Optimization of RF-DC converters - Ribeiro, Helena Luísa Silva (2022)
This thesis presents, firstly, an analysis on the impacts of the diode's configuration in an RF-DC converter and how the frequency affects the converter. The two possible configurations for the diode are in shunt or series, there were designed two converters with these configurations, in which the experimental results obtained 49% efficiency at 0dBm in the series configuration and 41 % at 0 dBm in the shunt converter. Even though the series con- figuration has a better performance, it requires a choke block, in this way, the shunt converter is the most appealing diode configuration. As for the frequency analysis, it could be concluded that when the frequency increases the diode has more difficulty rectifying the RF signal, so its performance decreases. Secondly, the impacts on the impedance seen by the diode were also analysed through a source pull simulation, which concluded that the diode requires a high impedance from the source. To provide more evidence to the source pull simulation, two different RF-DC converters were compared, the first one used the results from the source pull to design the converter, the second one used the traditional complex conjugate method. Even though the efficiencies obtained from the experimental results were not as high as possible, they were very satisfactory. With the high impedance converter achieving 33 % efficiency and the complex conjugate converter only 3 %, with this, it is possible to conclude that the source pull method with high impedance improves significantly the diode's performance.